2021
DOI: 10.1021/acs.inorgchem.1c02982
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insight into Complexation Ability and Coordination of Uranyl Nitrate by 1,10-Phenanthroline-2,9-diamides

Abstract: Reprocessing of spent nuclear fuel (SNF) is an important task in a frame of ecology and rational use of natural resources. Uranium, as the main component of SNF (>95%), can be recovered for further use as fresh nuclear fuel. To minimize an amount of solid radioactive waste generated during SNF reprocessing, new extractants are under investigation. Diamides of 1,10-phenanthroline-2,9-dicarboxylic acid are perspective tetradentate N-donor ligands that form strong complexes with f-elements, which are soluble in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…DFT calculation of the [UO 2 L3(NO 3 )] + cation (PBE functional, full-electron relativistic TZ-basis, see the SI for details) showed that it is the most stable conformation that coincides with previously reported cation structures analyzed by XRD. 23,26,27 The optimized structure of the [UO 2 (NO 3 ) 3 ] − anion is in agreement with that calculated by the Japanese authors using the B3LYP functional. 17 Several structures on the PES of ion pair {[UO 2 L3(NO 3 )] + [UO 2 (NO 3 ) 3 ] − } corresponding to local minima were found by calculating the change in the energy of the system when a cation and anion, initially separated by a distance 15 Å, approach each other along certain trajectories by reducing the distance between them by a small step under complete variation of all other geometric parameters.…”
Section: ■ Results and Discussionsupporting
confidence: 86%
“…DFT calculation of the [UO 2 L3(NO 3 )] + cation (PBE functional, full-electron relativistic TZ-basis, see the SI for details) showed that it is the most stable conformation that coincides with previously reported cation structures analyzed by XRD. 23,26,27 The optimized structure of the [UO 2 (NO 3 ) 3 ] − anion is in agreement with that calculated by the Japanese authors using the B3LYP functional. 17 Several structures on the PES of ion pair {[UO 2 L3(NO 3 )] + [UO 2 (NO 3 ) 3 ] − } corresponding to local minima were found by calculating the change in the energy of the system when a cation and anion, initially separated by a distance 15 Å, approach each other along certain trajectories by reducing the distance between them by a small step under complete variation of all other geometric parameters.…”
Section: ■ Results and Discussionsupporting
confidence: 86%
“…20 Also the same ligand showed high affinity towards UO 2 2+ . 21 This fact can be associated with the ability of the pyrrolidine-derived ligands to predominantly have the conformation needed to form complexes with cations. [22][23][24][25][26] These results prompted us to continue the search for pyrrolidine-substituted diamides.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, such structural diversity permits fine-tuning of the ligand properties. Recently, serious attention has been paid to such phenanthroline diamides which have various substituents in the aromatic core, such as chlorine atoms [ 6 , 7 , 8 , 9 ], alkoxy groups [ 3 , 10 ], and others.…”
Section: Introductionmentioning
confidence: 99%